At multiple fronts: Diabetes stigma and weight stigma in adults with type 2 diabetes. Issue 1 (23rd September 2020) - Himmelstein, M. S.; Puhl, R. M.
Abstract: Aim: The diabetes and obesity fields have called for attention to the harmful role of stigma in obesity and diabetes, especially given that little is known about the extent and nature of diabetes stigma facing adults with type 2 diabetes, or the experience of weight stigma in this population. This study addresses this research gap by examining the prevalence and demographic correlates of weight stigma and diabetes stigma in individuals with type 2 diabetes. Methods: Adults ( N  = 1212, M age  = 52) with type 2 diabetes living in the USA were recruited by a healthcare‐oriented market research firm, and completed online questionnaires to assess their experiences with weight stigma and diabetes stigma, as well as their internalization of both forms of stigma. Rates of stigma and sociodemographic correlates (years with type 2 diabetes, age, education, income, gender, race and BMI) were examined. Results: More than half of participants reported prior experiences of weight stigma, and 40–60% reported experiencing weight stigma in a healthcare context. Participants reported frequent experiences with diabetes‐related stigma including blame and judgement, self‐stigma and differential treatment. Women reported more weight stigma than men, and White women appeared particularly at risk for experiencing weight and diabetes related stigma relative to Black women. Conclusions: Individuals with type 2 diabetes reported higher rates of weight stigma than the general population, experienced high rates of diabetes‐related stigma, and many internalized these forms of stigma. Increased attention to stigma reduction is essential to ensuring equitable care for individuals with type 2 diabetes.